Fruit pod extracts as a source of nutraceuticals and pharmaceuticals - Abdul Karim, Azila; Azlan, Azrina (MDPI, 2012)
Fruit pods contain various beneficial compounds that have biological activities and can be used as a source of pharmaceutical and nutraceutical products. Although pods or pericarps are usually discarded when consuming the edible parts of fruits, they contain some compounds that exhibit biological activities after extraction. Most fruit pods included in this review contain polyphenolic components that can promote antioxidant effects on human health. Additionally, anti-inflammatory, antibacterial, antifungal and chemopreventive effects are associated with these fruit pod extracts. Besides polyphenolics, other compounds such as xanthones, carotenoids and saponins also exhibit health effects and can be potential sources of nutraceutical and pharmaceutical components. In this review, information on fruit pods or pericarp of Garcinia mangostana, Ceratonia siliqua, Moringa oleifera, Acacia nilotica, Sapindus rarak and Prosopis cineraria is presented and discussed with regard to their biological activity of the major compounds existing in them. The fruit pods of other ethno- botanical plants have also been reviewed. It can be concluded that although fruit pods are considered as being of no practical use and are often being thrown away, they nevertheless contain compounds that might be useful sources of nutraceutical and other pharmaceutical components.